People’s interaction with attributes of public art in urban spaces - Yeo, Lee Bak (2014)
The fitting of public art in towns and cities around the world has become favourable and has gradually been used in urban regeneration schemes. As today people begin to appreciate public artworks by interacting with it. This study explores public art in palpable forms namely sculpture, mural and street furniture. Many researchers have studied on the value of art in public realm and its artistry toward aesthetic, economic, social and cultural claims. Several studies have been conducted on attributes of the artworks such as attractiveness, size, material composition, placement and its social identity. However, there is still a lack of study namely on size, material composition and the placement of public art that can contribute to people’s interaction, be it active or passive. This study began with an observation at Georgetown, Penang to garner a prerequisite understanding of the site and followed up with survey questionnaires (N=211) to generate the results of public art attributes, and eventually interviews (N=5) were adopted to strengthen the findings. The questionnaires were analysed using SPSS (Chi-square test) and AMOS (Confirmatory Factor Analysis) and observation and interview data were content analysed. The result suggests that people like to interact with a life-size public artwork, fabricated from natural and non-natural materials which located at streets, squares, plaza or parks. For those who took photos, touched or observed the artwork attentively, they are infused with positive vibes such as feeling pleasant, contented and excited. Whenever they felt positive, they are subsequently motivated to recommend their friends, family or relatives to visit the artworks. This research allows landscape architect, architect, urban planner, artwork producer, artist and local authority to understand the significance of adapting public art’s attributes structurally and socially that can contribute to the renewal of urban space.